From Acute to Chronic Tinnitus: Pilot Data on Predictors and Progression - Vielsmeier, Veronika; Santiago Stiel, Ryan; Kwok, Pingling; Langguth, Berthold; Schecklmann, Martin (Frontiers in Neurology, 2020)
Little is known about the transition from acute tinnitus to chronic tinnitus. By means of this study, we are attempting to close this gap by presenting prospective pilot data of patients with acute tinnitus, followed by tracking their condition's trajectory over a period of 6 months. Forty-nine patients presenting with acute tinnitus (duration < 28 days) were recruited in two clinics. We recorded demographic and clinical tinnitus-related data as well as data on personality, health, treatments, and life-style, during patients' first appearance in the clinic and again three and 6 months thereafter. Standard audiograms were performed at the first and the second visit. Nine (18.4%) patients showed full remission of their tinnitus. These patients differed from patients with a chronic course of tinnitus by shorter tinnitus duration, lower fear-related hyperacusis, higher proportion of female gender, increased ear pressure, and lower levels of alcohol consumption. Among the patients with a chronification of tinnitus, there was no change in tinnitus characteristics. However, their tinnitus distress improved moderately over time. These preliminary data are in line with earlier studies that have shown that only a small proportion of those patients presenting in the clinic with acute tinnitus experience a full remission. The results of this study can be of service in deducing hypotheses for the transition from acute to chronic tinnitus and in developing designs for interventional studies.